PENGARUH METODE CARD SORT TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PPKN KELAS V SEKOLAH DASAR NEGERI 28 CAKRANEGARA - Indry Chayati; Khairun Nisa; Muhammad Sobri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to determine the effect of the Card Sort method on the learning outcomes of class V students on Civics learning content at SDN 28 Cakranegara. This research is experimental research to find the effect of the Card Sort method on student learning outcomes in Civics learning content. This type of research is quantitative research using the Quasy Experimental Design method, Nonequivalent Control Group Design type. The data collection methods used are observation, tests and documentation. Hypothesis testing uses T-test. The results of the research obtained t_count ≥ t_table, namely 12.034 ≥ 2.018 with a significance value (2-tailed) 0.000 ≤ 0.05, so Ho is rejected and Ha is accepted, meaning that there is an influence of the Card Sort method on the learning outcomes of class V students on Civics learning content at SDN 28 Cakranegara . The findings of this research indicate that the Card Sort method can be an alternative innovative learning method that is suitable for application at the elementary school education level, especially for subjects such as Civics which require a thorough understanding of concepts.